Post-challenge glycemia during pregnancy as a marker of future risk of type 2 diabetes: a prospective cohort study. (3rd July 2015) - Hakkarainen, Heidi; Huopio, Hanna; Cederberg, Henna; Pääkkönen, Mirja; Voutilainen, Raimo; Heinonen, Seppo
Abstract: The aim of this study was to evaluate the glycemic measures from an oral glucose tolerance test (OGTT) during pregnancy as predictors of incident type 2 diabetes mellitus (T2DM). Patients diagnosed with gestational diabetes mellitus (GDM) were divided into two groups according to the results of OGTT: one abnormal value = GDM1 ( n  = 338) and two abnormal values = GDM2 ( n  = 151), while women with normal glucose tolerance served as controls ( n =  385). Glucose tolerance was re-evaluated with an OGTT in a follow-up study (average follow-up time 7.3 ± 5.1 years). The incidence of T2DM after 10 years follow-up increased progressively by the degree of the glycemic abnormality during pregnancy: 0.8% in controls, 3.8% in GDM1 (adjusted HR 17.6, 95% CI 1.9–162.3) and 25.0% in GDM2 (adjusted HR 72.9, 95% CI 9.6–553.7), respectively ( p  = <0.0001). The risk of T2DM is significantly increased in women with two or more abnormal values in OGTT during pregnancy. Post-challenge glucose levels in OGTT were the best predictors of the incident T2DM in ROC analysis and they therefore identify the greatest risk group for targeted prevention of T2DM after GDM.